2019
DOI: 10.3390/cryst9020101
|View full text |Cite
|
Sign up to set email alerts
|

A New Half-Salamo-Based Homo-Trinuclear Nickel(II) Complex: Crystal Structure, Hirshfeld Surface Analysis, and Fluorescence Properties

Abstract: A new homo-trinuclear Ni(II) half-salamo-based complex [Ni3(L)2(μ-OAc)2(OAc)2(CH3OH)2]·2CH3OH was synthesized via the reaction of a tridentate ligand HL (2-[O-(1-ethyloxyamide)]oxime-4-bromophenol) and Ni(OAc)2·4H2O, and characterized using elemental analyses, IR spectra, UV-Vis absorption spectra, X-ray crystallography, and Hirshfeld analysis. Interestingly, single-crystal X-ray analysis showed that the two acetate molecules were bonded simultaneously with the Ni(II) atoms by mono-dentate chelating and bident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(23 citation statements)
references
References 63 publications
(62 reference statements)
1
22
0
Order By: Relevance
“…As is generally known, salen compound and its derivatives are a class of very important N 2 O 2 chelating ligands in inorganic chemistry [5], their metal complexes not only show a variety of catalytic and optical properties [6], but also have some advantages in the field of antibiosis, treatment of tumors, biological activities and so on [7]. Salamo compounds form metal complexes with interesting properties.…”
Section: Discussionmentioning
confidence: 99%
“…As is generally known, salen compound and its derivatives are a class of very important N 2 O 2 chelating ligands in inorganic chemistry [5], their metal complexes not only show a variety of catalytic and optical properties [6], but also have some advantages in the field of antibiosis, treatment of tumors, biological activities and so on [7]. Salamo compounds form metal complexes with interesting properties.…”
Section: Discussionmentioning
confidence: 99%
“…When the concentration of the Cu II ion increased gradually, the absorption peaks had evidently changed to 271 nm. Compared with the peak (266 nm) of the free ligand HL 1 , this absorption peak was red-shifted, and another absorption peak at 324 nm disappeared in the UV-Vis absorption spectrum of the Cu II complex, which indicated that the oxime nitrogen atoms of the ligand H 2 L 2 have coordinated to the Cu II ions [14,16].…”
Section: Crystal Structure Descriptionmentioning
confidence: 94%
“…In fact, the latter always assembled supramolecular structures through the formation of intermolecular hydrogen bondings involving solvent molecules [22,30,[35][36][37]. The intramolecular and intermolecular interactions of molecular crystal of the Cu II complex were explored further by surface analysis using the Crystal Explorer program [14]. The interactions in molecular crystal can be clearly observed.…”
Section: Supramolecular Interactions and Hirshfeld Surface Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Two kinds of cavities, N 2 O 2 and O 2 O 2 , are formed in salen‐like or salamo‐like organic ligands, and most transitional and rare earth metal ions can coordinate with the cavity to form mononuclear, multinuclear and heteropolynuclear salen‐like complexes. Compared to salamo‐like ligands, single‐armed salamo‐like ligands can produce more conformational changes and coordination polymers, as well as uncover new features. The transition from salamo‐like ligands to single‐armed salamo‐like ligands can provide a variable supramolecular configuration and also give rise to the ligand possessing new coordination characteristics.…”
Section: Introductionmentioning
confidence: 99%